Isolated peritoneal lymphomatosis defined as post-transplant lymphoproliferative disorder after a liver transplant: A case report - Kim, Hong Beum (World J Clin Cases, 2019)
BACKGROUND: Post-transplant lymphoproliferative disorder (PTLD) is a fatal complication of solid organ transplantation or allogenic hematopoietic stem cell transplantation that is associated with immunosuppressive therapy. Potential manifestations are diverse, ranging from reactive lymphoid hyperplasia to high-grade lymphoma. PTLD is usually of B-cell origin and associated with Epstein-Barr virus (EBV) infection. Herein, we describe a case of PTLD involving the peritoneal omentum. There has been only case of PTLD as a diffuse large B-cell lymphoma (DLBCL) in the peritoneum. CASE SUMMARY: The patient was a 62-year-old man who had been receiving immunosuppressive therapy with tacrolimus since undergoing a liver transplant 15 years prior. He reported that he had experienced abdominal discomfort and anorexia 1 month prior to the current admission. Abdominal pelvic computed tomography (CT) revealed peritoneal and omental mass-like lesions without bowel obstruction. Ultrasonography-guided biopsy was performed, and he was histologically diagnosed with EBV-negative DLBCL. Positron emission tomography (PET)-CT depicted peritoneum and omentum involvement only, without any lymphadenopathy or organ masses, including in the gastrointestinal tract. Six cycles of chemotherapy with a “R-CHOP“ regimen (rituximab-cyclophosphamide, doxorubicin, vincristine, prednisolone) were administered, and PET-CT performed thereafter indicated complete remission. CONCLUSION: This is the first report of isolated peritoneal lymphomatosis defined as PTLD in a liver transplant recipient.